2021
DOI: 10.3389/fphar.2021.688140
|View full text |Cite
|
Sign up to set email alerts
|

DL-3-n-Butylphthalide Attenuates Myocardial Hypertrophy by Targeting Gasdermin D and Inhibiting Gasdermin D Mediated Inflammation

Abstract: Pressure overload leads to a hypertrophic milieu that produces deleterious cardiac dysfunction. Inflammation is a key pathophysiological mechanism underpinning myocardial hypertrophy. DL-3-n-butylphthalide (NBP), a neuroprotective agent, also has potent cardioprotective effects. In this study, the potential of NBP to antagonize myocardial hypertrophy was evaluated in C57BL/6 mice in vivo and in rat primary cardiomyocytes in vitro. In mice, NBP treatment reduced cardiac hypertrophy and dysfunction in a transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
(55 reference statements)
1
12
0
1
Order By: Relevance
“…17 In our previous study, we showed that pharmacological inhibition of GSDMD reversed TAC-induced cardiac hypertrophy. 13,14 Despite these promising findings, the direct effect of GSDMD deficiency on myocardial hypertrophy and GSDMD-related downstream pathogenic mechanisms have not been fully elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 In our previous study, we showed that pharmacological inhibition of GSDMD reversed TAC-induced cardiac hypertrophy. 13,14 Despite these promising findings, the direct effect of GSDMD deficiency on myocardial hypertrophy and GSDMD-related downstream pathogenic mechanisms have not been fully elucidated.…”
mentioning
confidence: 99%
“…17 In our previous study, we showed that pharmacological inhibition of GSDMD reversed TACinduced cardiac hypertrophy. 13,14 Despite these promising findings, the direct effect of GSDMD deficiency on myocardial hypertrophy and GSDMD-related downstream pathogenic mechanisms have not been fully elucidated. STING (stimulator of interferon genes), as an integral adaptor protein of innate immunity, can recognize both the classical second messengers produced by pathogenic microorganisms and nonclassical cyclic GMP-AMP (cGAMP) produced by the DNA sensor cGAS (cyclic GMP-AMP synthase) and cytosolic DNA.…”
mentioning
confidence: 99%
“…The signal transduction mechanism underlying MH is complex. Inflammation ( 70 ) and oxidative stress ( 71 ) have both been previously demonstrated to cause alterations leading to MH and heart failure. A previous systematic study of Wnt on a genome-wide level reported an association between MH and the Wnt expression profile ( 72 ).…”
Section: Discussionunclassified
“…For instance, Fu et al showed that the NLRP3 inhibitor MCC950 and caspase-1 i n h i b i t o r A c -Y V A D -C M K a m e l i o r a t e d i n c r e a s e d hippocampal neuronal pyroptosis and reduced the levels of pro-inflammatory cytokines and rescued cognitive deficits in mice with sepsis-associated encephalopathy (Fu et al, 2019). Besides, there are several drugs reported to target GSDMD directly and block pyroptosis, including necrosulfonamide (NSA), disulfiram and DL-3-n-butylphthalide (Rathkey et al, 2018;Hu et al, 2020;Han et al, 2021). For instance, Rathkey et al reported that NSA treatment attenuated release of inflammatory cytokine and significantly prolonged survival in a mouse model of sepsis, providing the basis for developing novel therapies for sepsis and other inflammatory diseases (Rathkey et al, 2018).…”
Section: Pyroptosis As a Therapeutic Target In Sepsismentioning
confidence: 99%